Binding affinity screening of polyphenolic compounds in Stachys affinis extract (SAE) for their potential antioxidant and anti-inflammatory effects - Hun Hwan Kim; Se Hyo Jeong; Min Yeong Park; Pritam Bhangwan Bhosale; Abuyaseer Abusaliya; Sang Joon Lee; Jeong Doo Heo; Hyun Wook Kim; Je Kyung Seong; Dong Il Kim; Kwang Il Park; Gon Sup Kim (Scientific Reports)
Abstract Free radical is a marker in various inflammatory diseases. The antioxidant effect protects us from this damage, which also plays an essential role in preventing inflammation. Inflammation protects the body from biological stimuli, and pro-inflammatory mediators are negatively affected in the immune system. Inflammation caused by LPS is an endotoxin found in the outer membrane of Gram-negative bacteria, which induces immune cells to produce inflammatory cytokines such as cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase. Based on this, the antioxidant and anti-inflammatory effects of plant extracts were investigated. First, the main phenolic compounds for the five peaks obtained from Stachys affinis extract (SAE) were identified. The antioxidant effect of each phenolic compound was confirmed through HPLC analysis before and after the competitive binding reaction between DPPH and the extract. Afterward, the anti-inflammatory effect of each phenolic compound was confirmed through competitive binding between COX2 and the extract in HPLC analysis. Lastly, the anti-inflammatory effect of SAE was confirmed through in vitro experiments and also confirmed in terms of structural binding through molecular docking. This study confirmed that phenolic compounds in SAE extract have potential antioxidant and anti-inflammatory effects, and may provide information for primary screening of medicinal plants.